Prickle and Strabismus form a functional complex to generate a correct axis during planar cell polarity signaling. - Jenny, A.; Darken, R.S.; Wilson, P.A.; Mlodzik, M. (The EMBO Journal, 2003)
Frizzled (Fz) signaling regulates the establishment of planar cell polarity (PCP). The PCP genes prickle (pk) and strabismus (stbm) are thought to antagonize Fz signaling. We show that they act in the same cell, R4, adjacent to that in which the Fz/PCP pathway is required in the Drosophila eye. We demonstrate that Stbm and Pk interact physically and that Stbm recruits Pk to the cell membrane. Through this interaction, Pk affects Stbm membrane localization and can cause clustering of Stbm. Pk is also known to interact with Dsh and is thought to antagonize Dsh by affecting its membrane localization. Thus our data suggest that the Stbm/Pk complex modulates Fz/Dsh activity, resulting in a symmetry-breaking step during polarity signaling.